Analisis Kualitas Pelayanan Menggunakan Pendekatan Lean Service dan Service Performance (Studi Kasus: Bank X) - Liora Darista Zahra; Dwi Sukma Donoriyanto (Ekonomis: Journal of Economics and Business, 2023)
Bank X is a State-Owned Enterprise and operates in the banking sector. This bank is the largest financial institution in Indonesia when viewed from the total value of assets under management. But in its implementation, Bank X received several complaints from customers over the services provided This study's goal is to determine the extent of the services' level of quality and waste mapping using Service Performance and Lean Service methods and also provide appropriate improvement proposals. This research begins with data collection, questionnaire distribution, analyzing data with the service Performance method to find the quality of Bank X services, mapping waste from the service activities provided then determining the root cause of the problem and given improvement recommendations. Based on the outcomes of service performance methods, the percentage of customer satisfaction with the quality of Bank X's services was 80.516%, which means clients are content with the level of service they receive The attributes included in the priority are, has modern banking equipment (X2) and has supporting facilities and service facilities that are comfortable and clean and adequate (X3). While the results of processing about lean service are known to be critical waste is waiting 21% and unclear communication 21%.